Cheese factory - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
François Tron writes that the cheese factory Fromagerie Fivatsy (at BP 17, Ambatomanga, Manjakandriana 116, Madagascar) is looking for partners to help ensure their continuity. 'We are a small-size cheese factory, 30 km east of Antananarivo, the...